"Why me, Lord?" : some social factors associated with the receipt of a donor heart in South Africa - Hartle, Raymond (Rhodes University, Faculty of Humanities, Department of Sociology, 2020)
Since the first human-to-human heart transplant in the world was performed by Prof Chris Barnard in Cape Town in 1967, heart transplantation has become the gold standard to treat people suffering from end stage heart failure. This thesis explores heart recipients' perceptions and experiences of their chronic heart illness before and after transplantation. It examines the medical experience in terms of the clinical diagnosis, the standard of communication about the illness and the proposed treatment, and the post-transplant regime. It also reflects how recipients make sense of heart disease and learn to live with a transplanted heart. The thesis also shows the extent to which the recipients' culture and individual identity impact such complex medical issues as end stage heart failure and transplantation. Qualitative research was undertaken in private sector heart transplant programmes in South Africa. The study is underpinned by Mishel's (1990) uncertainty theory as well as by social constructionism.
Keywords: Heart -- Transplantation -- Social aspects; Heart -- Transplantation -- Recipients -- Psychology; Heart -- Transplantation -- South Africa; Chronic diseases -- Psychological aspects